Focal Congenital Hyperinsulinism as a Cause for Sudden Infant Death. (January 2019) - Chinoy, Amish; Banerjee, Indraneel; Flanagan, Sarah E; Ellard, Sian; Han, Bing; Mohamed, Zainab; Dunne, Mark J; Bitetti, Stefania
Congenital hyperinsulinism (CHI) is the commonest cause of persistent and severe hypoglycemia in infancy due to unregulated insulin secretion from pancreatic β-cells. Prompt early diagnosis is important, as insulin reduces glucose supply to the brain, resulting in significant brain injury and risk of death. Histologically, CHI has focal and diffuse forms; in focal CHI, an inappropriate level of insulin is secreted from localized β-cell hyperplasia. We report a 4-month-old male infant, who presented with sudden illness and collapse without a recognized cause and died. Postmortem examination revealed pancreatic histopathology compatible with focal CHI. Immunofluoresence staining showed limited expression of p57 kip2 β-cells reinforcing the diagnosis. Mutation testing for genes associated with CHI from DNA from the focal lesion was negative. This case highlights the recognition of focal CHI as a possible cause for sudden infant death. In children dying suddenly and unexpectedly, postmortem pancreatic sections should be carefully examined for focal CHI.